Evaluating Sleepiness-Related Daytime Function by Querying Wakefulness Inability and Fatigue: Sleepiness-Wakefulness Inability and Fatigue Test (SWIFT) - Sangal, R. Bart (American Academy of Sleep Medicine, 2012)
STUDY OBJECTIVES: Routine assessment of daytime function in Sleep Medicine has focused on “tendency to fall asleep” in soporific circumstances, to the exclusion of “wakefulness inability” or inability to maintain wakefulness, and fatigue/tiredness/lack of energy. The objective was to establish reliability and discriminant validity of a test for wakefulness inability and fatigue, and to test its superiority against the criterion standard for evaluation of sleepiness—the Epworth Sleepiness Scale (ESS). METHODS: A 12-item self-administered instrument, the Sleepiness-Wakefulness Inability and Fatigue Test (SWIFT), was developed and administered, with ESS, to 256 adults ≥ 18 years of age (44 retook the tests a month later); consecutive patients with symptoms of sleep disorders including 286 with obstructive sleep apnea ([OSA], apnea-hypopnea index ≥ 5/h sleep on polysomnography [PSG]), 49 evaluated with PSG and multiple sleep latency test for narcolepsy and 137 OSA patients treated with continuous positive airway pressure (CPAP). RESULTS: SWIFT had internal consistency 0.87 and retest intraclass coefficient 0.82. Factor analysis revealed 2 factors—general wakefulness inability and fatigue (GWIF) and driving wakefulness inability and fatigue (DWIF). Normal subjects differed from patients in ESS, SWIFT, GWIF, and DWIF. SWIFT and GWIF (but not DWIF) had higher area under ROC curve, Youden's index, and better positive and negative likelihood ratios than ESS. ESS, SWIFT, GWIF, and DWIF improved with CPAP. Improvements in SWIFT, GWIF, and DWIF (but not ESS) were significantly correlated with CPAP compliance. CONCLUSIONS: SWIFT is reliable and valid. SWIFT and its factor GWIF have a discriminant ability superior to that of the ESS. CITATION: Sangal RB. Evaluating sleepiness-related daytime function by querying wakefulness inability and fatigue: Sleepiness-Wakefulness Inability and Fatigue Test (SWIFT). J Clin Sleep Med 2012;8(6):701-711.